Results of Fixed Points for Some Contractive Maps in Banach Spaces - Alfred, Olufemi Bosede (2015)
This study investigated the approximation of fixed points in relation to the notion of approximate operator and their various contractive maps in Banach spaces on Picard, Mann and Ishikawa iterations with the aim of establishing new results, extending and generalizing some of the existing results in literature. This study also investigated some new convergence conditions with the aim of getting some entirely new convergence results on Picard, Mann and Isikawa iterations in Banach spaces.